COVID‐19 and psychopathology of patients with intellectual disability. Issue 3 (9th August 2022) - Javaid, Amir; Javed, Eimen; Michael, Dasari
Abstract : People with intellectual disability (ID) are much more vulnerable to psychiatric illnesses than the general population and as such the pandemic has most likely affected their mental health. The mental health of patients with ID has been affected due to factors such as reduction in staffing levels due to illness, day services and respite care being closed, restrictions to visits and to going out to public places. This case series explores the mental health implications that contracting COVID‐19 had on five patients with ID attending an intellectual disability psychiatry service and reflects upon key messages for clinical practice.